Volumetric evaluation of pharyngeal segments in obstructive sleep apnea patients, - Rodrigues,Marcos Marques (2018)
Abstract Introduction Obstructive sleep apnea occurs by recurrent collapse of the upper airway during sleep, resulting in total (apnea) or partial (hypopnea) reduction of the airflow and has intimate relation with changes in the upper airway. Cone Beam CT allows the analysis of the upper airway and its volume by three-dimensional reconstruction. Objective To evaluate a possible correlation between the volume of the upper airway and the severity of the obstructive sleep apnea. Methods A retrospective study was performed reviewing polysomnographic data and Cone Beam CT records of 29 patients (13 males and 16 females). The correlation between the volume of the nasopharynx, the oropharynx and the total superior pharynx with the AHI was assessed by Pearson's rank correlation coefficient. Results The obstructive sleep apnea severity division was: ten patients had severe, 7 had moderate, 6 had mild and 6 of them were healthy. The correlation between the nasopharynx, the oropharynx and the total superior pharynx volumes and the Apnea-Hypopnea-Index was respectively: −0.415 (p = 0.025), 0.186 (p = 0.334) and −0329 (p = 0.089). The Spearman's rank controlled by the Body Mass Index, the age and the gender was: −0.206 (p = 0.304), −0.155 (p = 0.439) and 0.242 (p = 0.284). Conclusion There is no correlation between the volume of the airway and the obstructive sleep apnea, assessed by Apnea-Hypopnea-Index and controlled by the Body Mass Index, the age and the gender. The volume of the upper airways as an isolated parameter did not correlate to the severity of the obstructive sleep apnea syndrome, and should be evaluated together with other factors.